A Facile and Novel Synthesis of Ag-Graphene-Based Nanocomposites - Pasricha, Renu; Gupta, Shweta; Srivastava, Avanish Kumar (Small (Weinheim an der Bergstrasse, Germany), 2009)
Nanospacers for graphene: A facile and scalable process for the synthesis of aqueous solutions of isolated silver‐decorated graphene sheets (see image) is presented. The silver–graphene nanocomposite film shows a 109‐fold increase in electrical conductivity as compared to the graphite oxide film.